Studying the Protective Effect of Gundelia L. Against Induced Liver Diseases in Male Rats - Bdaiwi, Lelas Farhan (Scientific Journal for Faculty of Science-Sirte University, 2024)
<thead> The plant (Gundelia tournefortii) L (GL) was found in the temperate regions of Western Asia. Historically, it has been employed for its therapeutic attributes and biological efficacy in addressing diverse ailments. This study aimed to explore the protective role of GL. against the harmful effects of ethanol. Twenty-five male rats were split into five groups: the control group, the ethanol group, and other groups received GL. extracts containing flavonoids, alkaloids, and oils. The results demonstrated that treating the rats with ethanol caused elevating the activity of liver enzymes such as alkaline phosphatase, aspartate transaminase, alanine transaminase, gamma-glutamyl transferase, the concentrations of triglycerides, total cholesterol, low density lipoprotein, very low density lipoprotein, malondialdehyde, and reducing the concentrations of high density lipoprotein, total protein, albumin, glutathione, antioxidant enzymes activity like catalase, glutathione peroxidase, superoxide dismutase. Conversely, GL extracts reduced the toxicity of ethanol by decreasing the activity of liver enzymes, the concentration of triglycerides, total cholesterol, low density lipoprotein, very low density lipoprotein, malondialdehyde and elevating the concentrations of total protein, albumin, high density lipoprotein and antioxidant enzymes activity in the groups treated with these extracts. These results showed the hepatoprotective effects of GL extracts against ethanol which attributed to their antioxidant capacity. </thead>